Chinese Ibsenism: Reinventions of Women, Class and Nation - Tam, Kwok-Kan (Springer, 2019)

Fate and Prognostication in the Chinese Literary Imagination - Lackner, Michael; Tam, Kwok-Kan; Gänßbauer, Monika; Siu Han Yip, Terry (Brill, 2020)
The essays collected in Fate and Prognostication in the Chinese Literary Imagination deal with the philosophical, psychological, gender and cultural issues in the Chinese conception of fate as represented in literary texts and films, with a focus placed on human efforts to solve the riddles of fate prediction. Viewed in this light, the collected essays unfold a meandering landscape of the popular imaginary in Chinese beliefs and customs. The chapters in this book represent concerted efforts in research originated from a project conducted at the International Consortium for Research in the Humanities at the Friedrich-Alexander-University Erlangen-Nuremberg, Germany. Contributors are Michael Lackner, Kwok-kan Tam, Monika Gaenssbauer, Terry Siu-han Yip, Xie Qun, Roland Altenburger, Jessica Tsui-yan Li, Kaby Wing-Sze Kung, Nicoletta Pesaro, Yan Xu-Lackner, and Anna Wing Bo Tso. <br

Fully Printed Infrared Photodetectors from PbS Nanocrystals with Perovskite Ligands - Yousefiamin, Amirabbas; Killilea, Niall Andrew; Sytnyk, Mykhailo; Maisch, Philipp; Tam, Kwok-Kan; Egelhaaf, Hans-Joachim; Langner, Stefan; Stubhan, Tobias; Brabec, Christoph; Rejek, Tobias; Halik, Marcus; Poulsen, Katharina; et al. (ACS nano, 2019)
Colloidal nanocrystals from PbS are successfully applied in highly sensitive infrared photodetectors with various device architectures. Here, we demonstrate all-printed devices with high detectivity (similar to 10(12) cm Hz(1/2) /W) and a cut-off frequency of >3 kHz. The low material consumption (<0.3 mg per detector) and short processing time (14 s per detector) enabled by the automated printing promises extremely low device costs. To enable all-printed devices, an ink formulation was developed based on nanocrystals stabilized by perovskite-like methylammonium iodobismuthate ligands, which are dispersed in a ternary solvent. Fully inkjet printed devices based on this solvent were achieved with printed silver electrodes and a ZnO interlayer. Considerable improvements were obtained by the addition of small amounts of the polymer poly(vinylpyrrolidone) to the ink. The polymer improved the colloidal stability of the ink and its film-formation properties and thus enabled the scalable printing of single detectors and detector arrays. While photoconductors were shown here, the developed ink will certainly find application in a series of further electronic devices based on nanocrystals from a broad range of materials.
Keywords: colloidal nanocrystals; infrared detectors; inkjet printing; PbS; solution processing

Ibsen, Power and the Self: Postsocialist Chinese Experimentations in Stage Performance and Film - Tam, Kwok-Kan (Novus Press, 2019)

Psychogeography and Cultural Negotiation in the Poetic Imagination of Hong Kong Canadian Identity - Tam, Kwok-Kan (TRANSCULTURAL STREAMS OF CHINESE CANADIAN IDENTITIES, 2014)
CRIS-Team WoS Importer:2020-09-25